SCIENTIFIC STUDY OF THE PROBLEM OF PROFESSIONAL ORIENTATION OF STUDENTS IN PSYCHOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses the relevance of the problem of vocational guidance among students of higher medical educational institutions, psychological aspects that are important for their future professional activities.